Comparison of methods for monitoring residual platelet reactivity after clopidogrel by point-of-care tests on whole blood in high-risk patients - Paniccia, Rita; Antonucci, Emilia; Maggini, Niccolò; Miranda, Marco; Gori, Anna Maria; Marcucci, Rossella; Giusti, Betti; Balzi, Daniela; Prisco, Domenico; Abbate, Rosanna (Thrombosis and Haemostasis, 2010)
Cardiovascular events are more frequent in high-risk coronary artery disease (CAD) patients on dual antiplatelet therapy with a residual platelet reactivity (RPR) than in those showing inhibition of ADP-inducible platelet activation. It is known that post-interventional RPR is a clinically important entity confirming it as a risk factor for thrombo-is-chaemic events. Multiple electrode platelet aggregometry (MEA) on whole blood has been recently proposed as a rapid tool to evaluate RPR in high-risk CAD patients on clopidogrel therapy. It was the aim of this study to detect RPR in 801 high-risk CAD patients on dual antiplatelet therapy comparing MEA with the VerifyNow P2Y12 assay on whole blood and classical light transmission aggregation (LTA) on plateletrich plasma. ADP (10 μM) was employed as agonist for MEA and LTA. The prevalence of RPR was 20.6% by MEA, 16.1% by LTA and 30.8% by VerifyNow. MEA showed a significant correlation (rho=0.62, p<0.0001) with VerifyNow and a moderate agreement (k=0.52, p<0.001) with 81.5% of concordant values. A significant correlation was found between MEA and LTA (rho=0.71, p<0.001) with a good agreement (k=0.63, p<0.001) and 88.8% of concordant values. MEA in relation to LTA showed a sensitivity of 80% and a specificity of 91%. MEA might represent a reliable method and valid alternative in comparison with other available platelet function assays. It might help to guide antiplatelet therapy and thus improve clinical outcome of high-risk CAD patients.
Keywords: Clopidogrel therapy; light transmission aggregometry; multiple elec-trode aggregometry; point-of-care testing; residual platelet reactivity